Penyuluhan Tentang Prilaku Hidup Bersih Dan Sehat Dalam Pencegahan Penyakit Menular Di Kelurahan 26 Ilir Palembang - Heriziana Hz; Santi Rosalina; Hamyatri Rawalillah (PPNI UNIMMAN, 2023)
One of the preventive measures to prevent infectious diseases is the implementation of family PHBS. Family PHBS includes giving birth assisted by health workers, giving the baby exclusive breast milk, weighing the baby every month, the baby getting basic immunizations, using clean water, the family following the family planning program, hypertension sufferers taking medication regularly, TB sufferers being treated regularly, all family members registered with JKN , family members with mental disorders are not neglected, use healthy latrines, and do not smoke in the house.